2016
DOI: 10.1194/jlr.m060061
|View full text |Cite
|
Sign up to set email alerts
|

Lactosylceramide contributes to mitochondrial dysfunction in diabetes

Abstract: This article is available online at http://www.jlr.orgCompelling epidemiological and clinical data indicate that diabetes mellitus increases the risk for cardiac dysfunction and heart failure independently of other risk factors, such as coronary disease and hypertension. Lipotoxicity is an important contributor to cardiac dysfunction in both type 1 ( 1, 2 ) and type 2 ( 3-6 ) diabetes, which are characterized by excessive accumulation of triacylglycerols, long-chain acyl-CoAs, diacylglycerols, and ceramides in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 97 publications
(134 reference statements)
1
38
1
Order By: Relevance
“…In fact, several reports indicate that CerS5 and CerS2 directly interact and that these interactions may augment catalytic activity (2,3,48). Moreover, these enzymes and their respective ceramide products have been identified in mitochondria (1,4,49). Our previous studies demonstrated that loss of function of CerS5 led to cell hypertrophy (2), which we did not observe in CerS2 knockdown in this study (data not shown), suggesting that each of these enzymes directly regulates distinct cell processes.…”
Section: Discussioncontrasting
confidence: 43%
“…In fact, several reports indicate that CerS5 and CerS2 directly interact and that these interactions may augment catalytic activity (2,3,48). Moreover, these enzymes and their respective ceramide products have been identified in mitochondria (1,4,49). Our previous studies demonstrated that loss of function of CerS5 led to cell hypertrophy (2), which we did not observe in CerS2 knockdown in this study (data not shown), suggesting that each of these enzymes directly regulates distinct cell processes.…”
Section: Discussioncontrasting
confidence: 43%
“…Moreover, modulation of lipid metabolism can restore the mitochondrial dysfunction seen in T1D. This is exemplified by Novgorodov and colleagues who increased lactosylceramide via knockdown of neutral ceramidase (Novgorodov et al 2016). As mentioned previously, Han and coworkers postulated that early changes in cardiolipin species play a causal role in the mitochondrial dysfunction seen in T1D, which results in an inability of mitochondria to deal with the excess lipid burden in this setting ).…”
Section: Cardiac Lipid Accumulation and Mitochondrial Functionmentioning
confidence: 85%
“…↑ Increased (Nielsen et al 2002, Ueno et al 2008, Pulinilkunnil et al 2013, Kuramoto et al 2014, Yan et al 2015, Novgorodov et al 2016 ↑ Increased (Bugger et al 2008, Basu et al 2009, Pulinilkunnil et al 2013 Glucose oxidation ↓ Decreased (Pulinilkunnil et al 2013) ↓ Decreased (Bugger et al 2008, Basu et al 2009) Fatty acid oxidation ↑ Increased (Pulinilkunnil et al 2013) ↑ Increased (Bugger et al 2008, Basu et al 2009) Pathways modulated Inflammation ↑ Increased (Westermann et al 2009) ↑ Increased (Wang et al 2013) ↑ Increased (Chavali et al 2014) Mitochondrial function Dysfunction/abnormal (Pulinilkunnil et al 2013, Xu et al 2013, Novgorodov et al 2016 Dysfunction/abnormal (Shen et al 2004, Ye et al 2004, Xie et al 2011, Vadvalkar et al 2013, Xu et al 2013 Dysfunction/abnormal (Bugger et al 2008(Bugger et al , 2009 (Continued) R233 Review r h ritchie and others Lipid metabolism and diabetic cardiomyopathy impaired folding of proinsulin leading to endoplasmic reticulum (ER) stress in pancreatic islets such that Akita mice exhibit progressive loss of beta-cells, which correlates with diabetes development. Hyperglycaemia is evident from 3 to 4 weeks of age.…”
Section: ) Cardiac Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In support, palmitoleic acid has a demonstrated ability to reduce inflammation and to improve insulin sensitivity (Chan et al, 2015;Dimopoulos et al, 2006). While the significance of changes in circulating lactosyl ceramides is less clear, recent evidence indicates that elevated lactosylcermide concentrations appear to be involved with mitochondrial respiration rates and calcium retention in diabetic mice (Novgorodov et al, 2016). Furthermore, Iwabuchi et al (2008) reported that lactoysl-ceramides are believed to be involved in lipid raft formation of neutrophils (Iwabuchi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%